Evaluating QR Code-Based Attendance System Using User Experience - Hamdani, Dani; Wibowo, Ari Purno Wahyu; Heryono, Heri (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2025)
Efficient attendance tracking and academic schedule management are critical for students and lecturers in higher education. However, many existing systems lack user-friendly interfaces and integrated functionality, resulting in inefficiencies and reduced user satisfaction. This study aims to develop and evaluate the user experience of ‘Attend’, a mobile application designed to address these challenges. The target population consisted of higher education students and lecturers, with 35 student respondents participating in the evaluation phase through interviews and focus group discussions (FGDs) to inform the design of an intuitive and functional interface prototype. The authors conducted usability testing using the Maze App to assess task completion efficiency, followed by a user experience evaluation using the User Experience Questionnaire (UEQ). The results showed that users were able to complete tasks efficiently, although some interface components required refinement. The UEQ scores showed 'Above Average' ratings for attractiveness, efficiency, dependability, and novelty. The app also received 'Good' ratings for perspicuity and stimulation for improving clarity. These findings suggest that Attend effectively meets the needs and expectations of users in academic settings. This study contributes to the development of mobile-based educational tools by demonstrating the importance of incorporating user feedback in the design process to improve usability and user satisfaction.